Perception of Online Teaching and Learning (T&L) Activities Among Postgraduate Students in Faculty of Health Sciences, Universiti Kebangsaan Malaysia (UKM) - Ghazali, Ahmad Rohi; Zainodin, Elly Liyana; Madhavan, Indira; Gnanasundram, Linsay Sundram; Nisar, Nadia; Abd Rashid, Reena; Muniandy, Subashini; Tang, Wei Wei (Frontiers in Education, 2022)
The COVID-19 pandemic has changed the landscape of teaching pedagogies, assessment methods, supervision, and student engagement in higher education institutions. Exploration of students’ perception on online teaching and learning (T&L) in terms of their level of satisfaction is an important core indicator of their acceptance to enhance the long-term impact of the online (T&L) activities. The objective of the study is to determine the level of satisfaction of online (T&L) activities and its involved technical support among postgraduate students in the Faculty of Health Sciences, Universiti Kebangsaan Malaysia (UKM). A validated questionnaire was used to conduct the survey. A total of 81 postgraduate students were recruited using purposive sampling in the study. Results showed that more than 86% of the students were satisfied with the online T&L activities except for two areas where 50% of the students felt that the curriculum structure design was too heavy and they felt stressed after attending the first online class and examination. On the other hand, more than 70% of the students were satisfied with the technical support for the online T&L. Although the satisfaction level for both was high, there was no association between them, χ2 (1, N = 162) = 3.8, p = 0.42. In conclusion, the postgraduate students of the Faculty of Health Sciences, UKM are satisfied with the online T&L process, which implies a good reception. A review of curriculum structure and design that considers the psychological and behavior changes among students during online T&L is also recommended for the online T&L continues to be effective in the future.